Hubungan Lagu Srikandi dan Motivasi Reflektif Inspirasi terhadap Mindset Wanita Bersemangat Wirausaha - Pranoto, Henry Susanto; Sitepu, Rismawati Br; Soeparto, Wahyudi Henky; Subagio, Hartono (JOM, 2024)
As an effort to optimize the function and role of women, researchers conducted a descriptive study to determine the relationship between the influence of the song "Srikandi" and the influence of reflective inspirational motivation on the growth of entrepreneurial spirit in building a female entrepreneurial mindset. This study was conducted by collecting questionnaire data distributed to 14 respondents representing the Dharma Wanita Persatuan (DWP) LLDIKTI VII Surabaya. The results of the calculation of the study using the Pearson Correlation Coefficient showed a moderate negative (inverse) material correlation strength (r = -.45). The results of the study concluded that the meaning of the song "Srikandi" which has a melancholy nuance (minor) with expressive sad lyrics, shows the expression of beauty from the participants involved. However, the deep expressive results of the songs provide a negative (weakening) reflective inspirational motivational influence on the growth of entrepreneurial spirit in building a female entrepreneurial mindset.